Estimating post-release mortality of European sea bass based on experimental angling. (17th January 2018) - Lewin, Wolf-Christian; Strehlow, Harry Vincent; Ferter, Keno; Hyder, Kieran; Niemax, Jan; Herrmann, Jens-Peter; Weltersbach, Marc Simon
Abstract: European sea bass ( Dicentrarchus labrax ) is an important target species for recreational and commercial fisheries. In recent years, the spawning stock biomass has declined markedly in some areas, and strict management measures have been introduced. However, the development of appropriate stock assessment and fisheries management has been hampered by a lack of information on post-release mortality. This study investigated post-release mortality of sea bass captured with common recreational fishing gear under experimental conditions in an aquaculture facility over 10 d. Three experiments investigated: (i) the effects of different bait types; (ii) the impact of prolonged air exposure; and (iii) the impact of deep hooking on post-release mortality. By combining the experimental results with country-specific information on sea bass angling practices, estimates of post-release mortality are provided for the northern sea bass stock. No mortality was observed for sea bass captured on artificial baits. The use of natural baits resulted in a mortality of 13.9% (95% CI  = 4.7–29.5%), which was associated with deep hooking, hooking injuries, and prolonged air exposure. The use of artificial baits and short air exposure (≤30 s) increased survival probability, whereas deep hooking resulted in 76.5% (95% CI  = 50.0–93.2%) mortality. Depending on country-specific angling practices, post-release mortality estimates ranged from 2.8% to 9.1% (mean = 5.0%, 95% CI  = 1.7–14.4%) for northern sea bass. Despite these relatively low mortality estimates, post-release mortality should be considered in stock assessments as its cumulative impact may be high. Moreover, post-release mortality can be reduced by implementing species-specific best practice guidelines.